High dose concentration administration of ascorbic acid inhibits tumor growth in BALB/C mice implanted with sarcoma 180 cancer cells via the restriction of angiogenesis - Lee Hye; Yi Sang-Yeop; Park Seyeon; Yu Jaelim; Park Jin-Hee; Lee Gunsup; Yeom Chang-Hwan; Hong Young; Yang Joosung; Lee Sukchan (Journal of Translational Medicine, 2009)
Abstract To test the carcinostatic effects of ascorbic acid, we challenged the mice of seven experimental groups with 1.7 × 10-4 mol high dose concentration ascorbic acid after intraperitoneal administrating them with sarcoma S-180 cells. The survival rate was increased by 20% in the group that received high dose concentration ascorbic acid, compared to the control. The highest survival rate was observed in the group in which 1.7 × 10-4 mol ascorbic acid had been continuously injected before and after the induction of cancer cells, rather than just after the induction of cancer cells. The expression of three angiogenesis-related genes was inhibited by 0.3 times in bFGF, 7 times in VEGF and 4 times in MMP2 of the groups with higher survival rates. Biopsy Results, gene expression studies, and wound healing analysis in vivo and in vitro suggested that the carcinostatic effect induced by high dose concentration ascorbic acid occurred through inhibition of angiogenesis.